2012
DOI: 10.1002/nme.4398
|View full text |Cite
|
Sign up to set email alerts
|

A cohesive element model for mixed mode loading with frictional contact capability

Abstract: SUMMARY We present a model that combines interface debonding and frictional contact. The onset of fracture is explicitly modeled using the well‐known cohesive approach. Whereas the debonding process is controlled by a new extrinsic traction separation law, which accounts for mode mixity, and yields two separate values for energy dissipation in mode I and mode II loading, the impenetrability condition is enforced with a contact algorithm. We resort to the classical law of unilateral contact and Coulomb friction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 37 publications
3
58
0
1
Order By: Relevance
“…(27). The laws obtained in this way are similar to those presented by Snozzi and Molinari [93], who used the constants in a slightly different way. For the case G II /G I = 2, Eq.…”
Section: Damaged Interface: Cohesive Traction-separation Lawssupporting
confidence: 77%
See 2 more Smart Citations
“…(27). The laws obtained in this way are similar to those presented by Snozzi and Molinari [93], who used the constants in a slightly different way. For the case G II /G I = 2, Eq.…”
Section: Damaged Interface: Cohesive Traction-separation Lawssupporting
confidence: 77%
“…In other words, if a potential traction-separation law is formulated, it is not possible to distinguish energetically between pure mode I and pure mode II, as the fracture energy is required to be independent from the fracture path. However, as pointed out by some authors [92,93], it is reasonable to assume that the work of decohesion should be path dependent, as the energy dissipated in a fracture process depends on some microstructural details that inherently make mode II different from mode I, at least at a macroscopic level. In the framework introduced above, the fracture energy path-dependency can be achieved by simply discarding Eq.…”
Section: Damaged Interface: Cohesive Traction-separation Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the shake table tests were stopped prematurely and hence no conclusions regarding the drift capacities at horizontal and vertical load failure under dynamic loads were possible. A numerical study by Snozzi and Molinari (2013) showed that the strength of URM walls is larger when subjected to higher strain rates due to a more diffuse cracking pattern. However, this study did not yield any information regarding the effect of the strain rate on the deformation capacity since the bricks were modelled as elastic.…”
Section: Quasi-static Vs Dynamic Testsmentioning
confidence: 99%
“…The mechanism of the damage process of cohesive elements is important especially for mixed mode loading [41]. Recently, an increasing interest has been devoted to combining cohesive damage with frictional contact [41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%